The prevalence of bacteremia in out of hospital cardiac arrest patients presenting to the emergency department of a tertiary care hospital. (1st January 2021) - Abou Dagher, Gilbert; Bou Chebl, Ralph; Safa, Rawan; Assaf, Mohammad; Kattouf, Nadim; Hajjar, Karim; El Khuri, Christopher; Berbari, Iskandar; Makki, Maha; El Sayed, Mazen
Abstract: Background: Out-of-hospital cardiac arrest (OHCA) remains one of the most common causes of death. There is a scarcity of evidence concerning the prevalence of bacteraemia in cardiac arrest patients presenting to the Emergency Department (ED). We aimed to determine the prevalence of bacteraemia in OHCA patients presenting to the ED, as well as study the association between bacteraemia and in-hospital mortality in OHCA patients. In addition, the association between antibiotic use during resuscitation and in-hospital mortality was examined. Methods and results: This was a study of 200 adult OHCA patients who presented to the ED between 2015 and 2019. Bacteraemia was confirmed if at least one of the blood culture bottles grew a non-skin flora pathogen or if two blood culture bottles grew a skin flora pathogen from two different sites. The prevalence of bacteraemia was 46.5%. Gram positive bacteria, specifically Staphylococcus species, were the most common pathogens isolated from the bacteremic group. 42 patients survived to hospital admission. The multivariate analysis revealed that there was no association between bacteraemia and hospital mortality in OHCA patients (OR = 1.3, 95% CI= 0.2–9.2) with a p -value of .8. There was no association between antibiotic administration during resuscitation and hospital mortality (OR = 0.6, 95% CI= 0.1 − 3.8) with a p -value of .6. Conclusion: In our study, the prevalence of bacteraemia among OHCA patients presenting to the ED was found to be 46.5%. Bacteremic and non-bacteremic OHCA patients had similar initial baseline characteristics and laboratory parameters except for higher serum creatinine and BUN in the bacteremic group. In OHCA patients who survived their ED stay there was no association between hospital mortality and bacteraemia or antibiotic administration during resuscitation. There is a need for randomised controlled trials with a strong patient oriented primary outcome to better understand the association between in-hospital mortality and bacteraemia or antibiotic administration in OHCA patients. KEY MESSAGES: We aimed to determine the prevalence of bacteraemia in OHCA patients presenting to the Emergency Department. In our study, we found that 46.5% of patients presenting to our ED with OHCA were bacteremic. Bacteremic and non-bacteremic OHCA patients had similar initial baseline characteristics and laboratory parameters except for higher serum creatinine and BUN in the bacteremic group. We found no association between bacteraemia and hospital mortality. There was no association between antibiotic administration during resuscitation and hospital mortality. There is a need for randomised controlled trials with a strong patient oriented primary outcome to better understand the association between in-hospital mortality and bacteraemia or antibiotic administration in OHCA patients.